Effectiveness of baby friendly hospital initiative implementation on timely initiation of breast feeding - a comparative study - Jacob, Sujamol; Seetha, Simi Prasadchandran; Sujatha, Yesodha (International Journal Of Community Medicine And Public Health, 2017)
Background: Breast milk is unquestionably the best milk for new born baby. As per UNICEF and WHO, immediate initiation and exclusive breast feeding for six months are essential for reducing infant and neonatal mortality and malnutrition and improving young child survival. In a study conducted by Indian Association of Pediatrics (IAP) in 2009 showed that there has been an alarming decline in breast feeding practices over years. This created great concern and Ministry of Health and Family Welfare decided to revive the BFHI programme, a global movement that aims to give every baby the best start in life by creating a health care environment where breast feeding is the norm. We, the Department of Obstetrics and Gynaecology, Sree Avittom Thirunal Hospital, Government Medical College, Trivandrum, Kerala conducted a study to compare the breast-feeding practices prior to and after implementation of BFHI programme. Methods: This was a comparative study done in 2013 -14 among 320 post-natal mothers delivered at SAT hospital before and after BFHI implementation to study the improvement in Breast feeding practices. Results: The revamping programme of BFHI brought significant change in timely initiation of breast feeding within one hour of delivery. Knowledge of mothers increased in the post implementation group. Proactive approach from the part of health workers also showed significant improvement. Conclusions: The campaign has initiated a positive response highlighting the benefits of breast feeding and dangers of bottle or animal milk feeding. A well-organized community awareness programme involving obstetrician, pediatrician and other health personnel will help in promotion of breast feeding through periodic review of the status and progress of the programme.